Comprehensive Characterization of Somatic Mutations Impacting lncRNA Expression for Pan-Cancer - Yue Gao; Xin Li; Hui Zhi; Yunpeng Zhang; Peng Wang; Yanxia Wang; Shipeng Shang; Ying Fang; Weitao Shen; Shangwei Ning; Steven Xi Chen; Xia Li (Elsevier, 2019)
Somatic mutations have long been recognized as an important feature of cancer. However, analysis of somatic mutations, to date, has focused almost entirely on the protein coding regions of the genome. The potential roles of somatic mutations in human long noncoding RNAs (lncRNAs) are therefore largely unknown, particularly their functional significance across different cancer types. In this study, we characterized some lncRNAs whose expression was affected by somatic mutations (defined as MutLncs) and constructed global MutLnc landscapes across 17 cancer types by systematically integrating multiple levels of data. MutLncs were commonly downregulated and carried low mutation frequencies and non-silent mutations in most cancer types. Co-occurrence analysis in pan-cancer highlighted combined patterns of specific MutLncs, suggesting that a number of MutLncs influence diverse cancer types through combination effects. Several conserved and cancer-specific functions of MutLncs were determined. We further explored the somatic mutations affecting lncRNA expression via mixed and unmixed effects, which led to specific functions in pan-cancer. Survival analysis indicated that MutLncs and co-occurrence pairs can potentially serve as cancer biomarkers. Clarification of the specific roles of MutLncs in human cancers could be beneficial for understanding the molecular pathogenesis of different cancer types and developing the appropriate treatments. Keywords: long noncoding RNAs, somatic mutation, pan-cancer, co-occurrence, mixed and unmixed effects, microRNA, methylation, gene